2020
DOI: 10.1093/cvr/cvaa161
|View full text |Cite
|
Sign up to set email alerts
|

Rare loss-of-function mutations of PTGIR are enriched in fibromuscular dysplasia

Abstract: Aims Fibromuscular dysplasia (FMD) and spontaneous coronary artery dissection (SCAD) are related, non-atherosclerotic arterial diseases mainly affecting middle-aged women. Little is known about their physiopathological mechanisms. We aimed to identify rare genetic causes to elucidate molecular mechanisms implicated in FMD and SCAD. Methods and Results We analyzed 29 exomes that included familial and sporadic FMD. We identifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Similarly, the HNRNPM and PTGIR proteins have been shown to promote cancerous cell growth and be associated with poorer oncogenic outcomes 65 , 66 . The latter is also involved with vascular remodeling, and its loss of function may increase risk for vessel stenosis and dissection 67 . If MAPK4 (TSS1500), HNRNPM , and PTGIR hypomethylation among smokers—what we observed—leads to greater protein expression, this could partially explain their increased risk for lung and heart diseases and several cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the HNRNPM and PTGIR proteins have been shown to promote cancerous cell growth and be associated with poorer oncogenic outcomes 65 , 66 . The latter is also involved with vascular remodeling, and its loss of function may increase risk for vessel stenosis and dissection 67 . If MAPK4 (TSS1500), HNRNPM , and PTGIR hypomethylation among smokers—what we observed—leads to greater protein expression, this could partially explain their increased risk for lung and heart diseases and several cancers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SLC24A3, which we identified through the TWAS analyses in tibial arteries to associate with FMD, encodes a transmembrane sodium/potassium/calcium exchanger also involved in calcium homeostasis 33 . The relevance of impaired vasodilation and/or enhanced vasoconstriction in FMD pathogenesis is supported by our recent study where we reported an enrichment among FMD patients for rare loss-offunction mutations in the gene encoding the receptor for prostacyclin, a major vasodilator hormone 34 . In line with these findings, impaired dilation of arteries in response to sublingual glyceryl trinitrate, a proxy for VSMC dysfunction, was reported in FMD patients, including in arterial segments clinically unaffected by the disease 35 .…”
Section: Discussionmentioning
confidence: 62%
“…In the majority of patients, SCAD is not an isolated event but is reflective of an underlying vascular, genetic, or as-yet undetected condition[ 24 ]. Accordingly, all patients who have experienced SCAD should undergo a complete vascular physical examination of the abdominal aorta, cervical carotid arteries, and arteries of the upper and lower extremities[ 25 ]. To search for FMD, we ordered a computed tomography (CT) angiogram of the aorta and renal arteries and duplex ultrasonography of extracranial carotid arteries, which showed normal-appearing arteries and were negative for FMD (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%